Religious Belief as an Independent Variable - Davidson, James D. 1942- (1972)
The author examines (1) the conditions under which religion is most likely to perform its comfort and challenge functions and (2) the extent to which religion today tends to perform these two functions. Evidence from Baptists and Methodists in two Indiana communities indicates that the comfort function is positively related to the maintenance of "vertical" beliefs, but is not associated with "horizontal" beliefs; the prophetic function is positively related to "horizontal" beliefs, but is negatively related to "vertical" beliefs. Finally, the data indicate that religion tends to provide comfort and support more than it inspires social protest and change.
Keywords: Baptists; Churches; Communities; Methodism; Neighborhoods; Questionnaires; Scientific Belief; Social beliefs